EFISIENSI PRODUKSI DAN ANALISIS RISIKO BUDIDAYA SELADA KERITING HIJAU DAN SELADA ROMAINE HIDROPONIK NFT (NUTRIENT FILM TECHNIQUE) DI PT XYZ, PROVINSI JAWA BARAT - Dian Eprianda; Fembriarti Erry Prasmatiwi; Ani Suryani (Lampung University, 2017)
This research aims to analyze the difference of production efficiency of green lettuce and romaine lettuce and difference of risk on green lettuce and romaine hydroponic Nutrient Film Technique(NFT) in PT XYZ. The data used in this research was monthly periodical data in the period of January until July 2015. Dependent variables are production of green lettuce and romaine lettuce and independent variables consist of harvest areas, seeds, rockwool, fertilizer A and B, and Labor. Data were analyzed using frontier production function and coefficient variation. The research showed that: there was a different of production efficiency between green lettuce and romaine lettuce using hydroponic NFT. Green lettuce has lower efficiency rate but higher risk than romaine lettuce because diseases such as withered fusarium infected green lettuce. Key words : efficiency, hydroponic, lettuce, production, risk, time series